Epidural use of meloxicam for the management of traumatic arthritis in bovines - GANGWAR, A K; DEVI, K H SANGEETA; SINGH, H N; MAURYA, S K; WAGHAYE, J Y (The Indian Journal of Animal Sciences, 2011)
Epidural use of lneloxicam in hock joint lameness was studied in cattle. Male crossbred calves (12), 18-20 ill0nths old were divided into 2 groups of 6 each. In test group 1 meloxicam @ 0.2 mg/kg b. wt. was injected into the lumbosacral epidural space after 2 h of turpentine oil injection and subsequently at 24 h interval up to 5 successive days. Meloxicam was well tolerated by animals without any side effects. No systemic or neuro toxicity was observed throughout the study. Study revealed that meloxicam can be used epidurally for treating hock joint lameness in bovines. Â